Performance enhancement among adolescent players after 10 weeks of pitching training with appropriate baseball weights - Yang, W.-W.; Liu, Y.-C.; Lu, L.-C.; Chang, H.-Y.; Chou, P. P.-H.; Liu, C. (The Journal of Strength and Conditioning Research, 2013)
Compared with regulation-weight baseballs, lightweight baseballs generate lower torque on the shoulder and elbow joints without altering the pitching movement and timing. This study investigates the throwing accuracy, throwing velocity, arm swing velocity, and maximum shoulder external rotation (MSER) of adolescent players after 10 weeks of pitching training with appropriate lightweight baseballs. We assigned 24 adolescent players to a lightweight baseball group (group L) and a regulation-weight baseball group (group R) based on their pretraining throwing velocity. Both groups received pitching training 3 times per week for 10 weeks with 4.4- and 5-oz baseballs. The players' throwing accuracy, throwing velocity, arm swing velocity, and MSER were measured from 10 maximum efforts throws using a regulation-weight baseball before and after undergoing the pitching training. The results showed that the players in group L significantly increased their throwing velocity and arm swing velocity (p < 0.05) after 10 weeks of pitching training with the 4.4-oz baseball, whereas group R did not (p > 0.05). Furthermore, the percentage change in the throwing velocity and arm swing velocity of group L was significantly superior to that of group R (p < 0.05). Thus, we concluded that the 10 weeks of pitching training with an appropriate lightweight baseball substantially enhanced the arm swing velocity and throwing velocity of the adolescent baseball players. These findings suggest that using a lightweight baseball, which can reduce the risk of injury without altering pitching patterns, has positive training effects on players in the rapid physical growth and technique development stage.